Inducirane pluripotentne matične celice pri odkrivanju in vrednotenju zdravilnih učinkovin - Rotman Primec, Jaka (Farmacevtski vestnik, 2025)
Induced pluripotent stem cells have become an important tool for drug discovery in recent years, offering significant advantages over traditional models, such as primary cells, cancer cell lines, and animal models. These cells are derived by reprogramming somatic cells into a pluripotent state, allowing differentiation into various cell types while retaining the genetic information of the individual. In drug discovery, models from induced pluripotent stem cells encompass twodimensional cultures, three-dimensional models, and more sophisticated organs-on-a-chip. These advanced models enable more accurate assessment of drug toxicity and efficacy, compound interactions, as well as detailed studies of disease mechanisms. however, challenges in application of induced pluripotent stem cells remain, including limited cellular maturity, variability across obtained cell lines, and high costs, which currently restrict their broader use in the pharmaceutical field. Despite these limitations, induced pluripotent stem cells hold great promise for the development of personalised therapies and the discovery of novel therapeutic approaches.
Keywords: celični modeli in vitro; inducirane pluripotentne matične celice; Matične celice; odkrivanje novih zdravilnih učinkovin; predklinične študije; Zdravilne učinkovine